PENGELOLAAN HUTAN BERBASIS KEARIFAN LOKAL DI DESA URAUR KECAMATAN KAIRATU, KABUPATEN SERAM BAGIAN BARAT, PROVINSI MALUKU - Tuharea, Rianti; Parera, Evelin; Silaya, Thomas M. (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
Local wisdom-based forest management represents a critical mechanism for maintaining forest resource sustainability through the integration of cultural values, customary regulations, and prudent utilization practices. This study aims to describe the forms of local wisdom, forest management systems, and the role of customary institutions in Uraur Village, Kairatu District, West Seram Regency. A qualitative descriptive method was employed through interviews, observations, and documentation involving customary leaders, village government officials, and local communities. The findings indicate that forest management in Uraur Village is grounded in various forms of local wisdom, including the sasi system (sola mapina, sola manawa, and sola kakehang) along with sanctions for violations, traditional management through area zonation and dusung cultivation patterns, the presence of the Kewang customary institution as forest guardians, and the cultural values of masohi and traditional rituals. The success of this management is determined by the strength of customary institutions in regulating culture-based forest utilization, community social solidarity, government policy support to reinforce the legitimacy of customary institutions to avoid jurisdictional overlaps, and comprehensive facilitation ranging from socialization and training to the implementation of sustainable forest management that considers socio-economic, ecological, cultural aspects, and local customary norms.